1991
DOI: 10.1038/jcbfm.1991.134
|View full text |Cite
|
Sign up to set email alerts
|

In vivo Binding of Nimodipine in the Brain: II. Binding Kinetics in Focal Cerebral Ischemia

Abstract: Summary:We report the binding characteristics of [3H]nimodipine to normal and ischemic brain in vivo, We used the 1,4-dihydropyridine, nimodipine, to label the L type voltage-sensitive calcium channel in focal cerebral ischemia after occlusion of both the middle cerebral and ipsilateral common carotid arteries in rats, Varying con centrations of [3H]nimodipine were infused 3,5 h after the onset of ischemia and circulated for 30 min before the brain was obtained for autoradiography and determina tion of regiona… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
10
0

Year Published

1991
1991
2013
2013

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 20 publications
(11 citation statements)
references
References 13 publications
1
10
0
Order By: Relevance
“…These results are consistent with our earlier observations of in vivo nimodipine binding in a model of irreversible focal ischemia (Hakim and Hogan, 199 1 ;Hogan et al, 1991). In that work increased nimodipine binding was first observed in regions with severe depression of CBF and was only later seen in regions the reperfused group (n = 11).…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…These results are consistent with our earlier observations of in vivo nimodipine binding in a model of irreversible focal ischemia (Hakim and Hogan, 199 1 ;Hogan et al, 1991). In that work increased nimodipine binding was first observed in regions with severe depression of CBF and was only later seen in regions the reperfused group (n = 11).…”
Section: Discussionsupporting
confidence: 92%
“…A blood sample was obtained at the time of decapitation, and 'H activity was determined using liquid scintillation counting. Metabolite concentration corrections following intravenous nimodipine administration have been previously determined in Sprague-Dawley rats (Hogan et al, 1991) and were used to calculate nimodipine concentrations in plasma and brain samples.…”
Section: Determination Of Nimodipine Bindingmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that after 5 minutes of ischemia the VSCCs are open, Ca ++ moves intracellularly, and specific binding of the VSCC antagonists increases in severely affected ischemic regions. 15 In vivo binding of dihydropyridine Ca ++ antagonists in ischemic brain tissue is to the high-affinity binding state of the L-type VSCC 19 that occurs in depolarized cell membranes. 39 The physiological importance of this binding is debatable; however, it is possible that this process is related to the improvement in histological outcome observed following early treatment with dihydropyridine Ca ++ antagonists.…”
Section: Discussionmentioning
confidence: 99%
“…Most clinical trials focus on nimodipine, but others like nilvadipine have also been studied. Nimodipine (Suwelack et al, 1985;Hogan et al, 1991;Wang et al, 2006) and nilvadipine (Takakura et al, 1992) penetrate the blood-brain barrier effectively, and therefore are convenient calcium channel blockers for testing a direct neuroprotective effect. …”
mentioning
confidence: 99%